Costly information acquisition in centralized matching markets - Rustamdjan Hakimov; Dorothea Kübler; Siqi Pan (Quantitative Economics, 2023)
When applying to a university, students and their parents devote considerable time acquiring information about university programs in order to form preferences. We explore ways to reduce wasteful information acquisition, that is, to help students avoid acquiring information about out-of-reach schools or universities, using a market design approach. Focusing on markets where students are ranked by universities based on exam scores, we find that, both theoretically and experimentally, a sequential serial dictatorship mechanism leads to higher student welfare than a direct serial dictatorship mechanism. This is because the sequential mechanism informs students about which universities are willing to admit them, thereby directing their search. Our experiments also show that the sequential mechanism has behavioral advantages because subjects deviate from the optimal search strategy less frequently than under the direct mechanism. Furthermore, providing historical cutoff scores under the direct mechanism can increase student welfare, especially when the information costs are high, although the observed effect is weaker than that of a sequential mechanism.
Keywords: C92; D47; 330; Matching market; deferred acceptance; serial dictatorship; information acquisition; game theory; lab experiment